Poéticas aprop(r)iadas: formas de reescritura y traducción en la obra de Héctor Hernández Montecinos - Omaña, Jesús Alexander Montoya (2020)
Héctor Hernández Montecinos (1979), is an author belonging to the generation called Novísimos poetas chilenos, who has reiteratedly practiced appropriation as a technique, especially in his book Debajo de la Lengua (2009), which contains more than 250 rewrites of Latin American authors. This dissertation aims to review the poetic work of Hernández Montecinos from the analysis of appropriation as rewriting and translation. For this purpose, in the first chapter, we investigate the concept of appropriation as a category that concerns multifaceted processes carried out in the poetry of the 21st century through a space proposed since the 20th century. We determined it when studying the poetics of Hernández Montecinos in Debajo de la Lengua (2009) as a set of relations that this poetics executes with those who appropriates, noticing its function through a contextual selection in which rewrites and co-autoreal procedures are created for the elaboration of an archive of Latin American poetry sources. In the second chapter, we examine the rewrites that Héctor Hernández Montecinos made through the appropriation of the book-object La poesía chilena (1978) by Juan Luis Martínez, which are found in the section "] lapoesíachilenasoyyo [" of [comma] in La Divina Revelación (2011), specifically those elaborated to the books Poema de Chile (1967), by Gabriela Mistral, and U (1926), by Pablo de Rokha. In this sense, we analyze the book-object of study of Juan Luis Martínez as a potential embryo for the appropriation poetics of Héctor Hernández Montecinos and its interference as a dialogue in a selection replica for the creation of modified utopias in the rewrites of Gabriela Mistral and Pablo de Rokha. Finally, in the third and final chapter, we study the translation made by Héctor Hernández Montecinos of the shamanic manifests of the Brazilian poet Roberto Piva: “Manifesto utópico-ecológico em defesa da poesia e do delírio” (1983), “Manifesto da selva mais próxima”(1984),“O século XXI me dará razão (se tudo não explodir antes)”(1984), in one of the sections of Debajo de la Lengua (2009), where it fictionalizes a language called “mutant portuñol ”, to which we investigated in the manifesto as a prolonged discursive genre from the avant-garde and its exploration as a hybrid and utopian language in the 21st century.